2010
DOI: 10.3727/096368910x494623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MRI Contrast Agents on the Stem Cell Phenotype

Abstract: The ultimate therapy for ischemic stroke is restoration of blood supply in the ischemic region and regeneration of lost neural cells. This might be achieved by transplanting cells that differentiate into vascular or neuronal cell types, or secrete trophic factors that enhance self-renewal, recruitment, long-term survival, and functional integration of endogenous stem/progenitor cells. Experimental stroke models have been developed to determine potential beneficial effect of stem/progenitor cell-based therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 55 publications
5
93
0
Order By: Relevance
“…Obviously, the low efficiency of loading the SPIO particles into cells and the cytotoxicity of previously formulated particles limit their usage as an image probe (21). It has been demonstrated by several groups that SPIO particles have little toxicity and few side effects on cell proliferation and activity (21,22). However, certain study results have indicated the inhibitory effect of SPIO particles on MSC differentiation and its signaling mechanism (23).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Obviously, the low efficiency of loading the SPIO particles into cells and the cytotoxicity of previously formulated particles limit their usage as an image probe (21). It has been demonstrated by several groups that SPIO particles have little toxicity and few side effects on cell proliferation and activity (21,22). However, certain study results have indicated the inhibitory effect of SPIO particles on MSC differentiation and its signaling mechanism (23).…”
Section: Discussionmentioning
confidence: 81%
“…Some investigators have already demonstrated the feasibility of in vivo tracking of transplanted MSCs by labeling them with magnetic SPIO particles (18)(19)(20). Obviously, the low efficiency of loading the SPIO particles into cells and the cytotoxicity of previously formulated particles limit their usage as an image probe (21). It has been demonstrated by several groups that SPIO particles have little toxicity and few side effects on cell proliferation and activity (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the partially complicated labeling protocols, simplified strategies using clinically approved materials (e. g. Endorem ® /Feridex ® , Superfect ® , Lipofectamine Plus ® , poly-Llysine (PLL), protamine) and low cell toxicity have been described in recent years [148,149]. While most studies do not describe any significant changes in cell behavior (e. g. apoptosis rate, proliferation index, differentiation behavior) [150,151], individual studies show changes in migration behavior and the ability to form colonies [152], in cell vitality [153], in differentiation behavior [154], or in the expression pattern [152]. By the same token, the influence of cell labeling on the long-term behavior of cells and the course of disease is currently unclear [155] and must be studied more closely in the future [156].…”
Section: Cell Labeling and Cell Imaging In Mrimentioning
confidence: 99%
“…61 In brief, MSC labeled with NPs were plated into six-well plates at 2,000 cells per well with complete growth medium and medium was changed every 2 days. The living cell population was assessed by automatic cell counting with the CASY Model TT, every 2 days from Day 2 to Day 10.…”
Section: Population Doubling Timementioning
confidence: 99%